Therapy of tungiasis: a double-blinded randomized controlled trial with oral ivermectin - Heukelbach,Jörg (2004)
Tungiasis is an ectoparasitosis causing considerable pathology in endemic areas. Standard therapy consists of removing the embedded parasite with a sterile needle. There is no effective chemotherapy at hand. To fill this gap, a double-blinded randomized controlled trial with oral ivermectin was conducted. A total of 54 individuals (27 in the placebo group, 27 in the ivermectin group) was followed up for seven days. They presented a total of 192 lesions. Patients received either ivermectin (300 µg/kg body weight at a single dose, repeated after 24 h) or placebo. Outcome measures included the clinical stage of lesion, presence of erythema, pain, itching, signs of viability of the parasite, and total lysis of flea. The ratio of fleas with total lysis per total number of fleas was slightly higher in the ivermectin group; however, this difference was not statistically significant. There was no significant difference in any of the other outcome measures between the treatment and the placebo group. The results show that oral ivermectin is without any clinically significant efficacy against embedded sand fleas at the dose given.